The impact of health anxiety on perceptions of personal and children's health in parents with Lynch syndrome. Issue 3 (14th January 2019) - Albiani, Jenna J.; McShane, Kelly E.; Holter, Spring; Semotiuk, Kara; Aronson, Melyssa; Cohen, Zane; Hart, Tae L.
Abstract: This study examined the differences in perceptions of one's health and one's child's health between parents with Lynch syndrome (LS) characterized with high versus low health anxiety. Twenty‐one parents completed semistructured telephone interviews about their perceptions of their own health and the health of their children. Qualitative content analysis using a template coding approach examined the differences between parents with high and low health anxiety. Findings revealed that the most prevalent difference emerged on perceptions of personal health, showing individuals with high health anxiety reported more extreme worries, were more hypervigilant about physical symptoms, experienced the emotional and psychological consequences of LS as more negative and severe, and engaged in more dysfunctional coping strategies than those with low health anxiety. Unexpectedly, with regards to perceptions of their children, parents in the high and low health anxiety groups exhibited similar worries. However, high health anxiety parents reported using dysfunctional coping about their children's health more frequently than those with low health anxiety. The findings suggest that health anxiety is of clinical significance for individuals with LS. Accurately identifying and treating health anxiety among this population may be one avenue to reduce the distress experienced by LS carriers.